Inter-Generational Organizational Communication Flow At Brimob Command Headquarters, Kelapa Dua, Depok - Fadhil Indrawan; Ahmad Toni (CV. AFDIFAL MAJU BERKAH, 2025)
Generational diversity in the modern work environment presents unique challenges in communication. Differences in values, preferences and work styles between generations can hinder collaboration and productivity. This article discusses the importance of effective intergenerational communication in modern organizational leadership. By understanding and addressing these communication challenges, organizations can create a more inclusive and productive work environment.